Identification of genes modified by N6-methyladenosine in patients with colorectal cancer recurrence - Zhu, Qianru; Huang, Xingxing; Yu, Shuxian; Shou, Lan; Zhang, Ruonan; Xie, Han; Liang, Zimao; Sun, Xueni; Feng, Jiao; Duan, Ting; Zhang, Mingming; Xiang, Yu; et al. (Frontiers in Genetics, 2022)
Background: Recent studies demonstrate that N6-methyladenosine (m6A) methylation performs a crucial role in Colorectal cancer (CRC). Therefore, we conducted a comprehensive analysis to assess the m6A modification patterns and identify m6A modified genes in patients with CRC recurrence. Methods: The m6A modification patterns were comprehensively evaluated by the NMF algorithm based on the levels of 27 m6A regulators, and tumor microenvironment (TME) cell-infiltrating characteristics of these modification patterns were systematically assessed by ssGSEA, CIBERSORT algorithms. The principal components analysis algorithm based on the m6A scoring scheme was used to explore the m6A modification patterns of individual tumors with immune responses. Weighted correlation network analysis, Univariable and Multivariable Cox regression were applied to identify m6A modified gene signatures. Single cell expression dataset of CRC samples was used to explore tumor microenvironment affected by these signatures. Results: Three distinct m6A modification patterns with significant recurrence-free survival (RFS) were identified in 804 CRC patients. TME characterization revealed that the m6A modification pattern with longer RFS exhibited robust immune responses. CRC patients were divided into high and low score subgroups according to m6A score individually, which was obtained from the m6A-related signature genes. The patients with low m6A scores had both longer RFS and overall survival (OS) with altered immune cell infiltration. Notably, m6A modified genes showed significant related to the prognosis of CRC patients in the meta-GEO cohort and TCGA cohort. Single cell expression indicated that ALVRL1 was centrally distributed in endothelial tip cells and stromal cells. Conclusions: The m6A modification plays an indispensable role in the formation of TME diversity and complexity. Importantly, the signatures (TOP2A, LRRC58, HAUS6, SMC4, ACVRL1, and KPNB1) were identified as an m6A-modified genes associated with CRC recurrence, thereby serving as a promising predictive biomarker or therapeutic target for patients with CRC recurrence.